Analisis Pengaruh Efisiensi Operasional, Arus Kas Operasi & Rasio Likuiditas Terhadap Financial Distress Pada Subsektor Hotel & Restoran - Nani Ernawati; Najwa, Rhaisya; Insan, Moch Rizaldy (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2025)
This research investigates the relationship between operational efficiency, measured by Total Assets Turnover (TATO), operating cash flow calculated using the indirect method, and liquidity proxied by the Current Ratio (CR), with financial distress measured using the Springate model (S-Score). The sample consists of hotel and restaurant subsector companies listed on the Indonesia Stock Exchange over the 2019–2023 period. Employing a quantitative approach, this study applies descriptive and explanatory analysis using secondary data derived from published annual financial statements. Panel data regression is utilized alongside classical assumption testing, as well as t-tests, F-tests, and the coefficient of determination (R²). The findings indicate that the independent variables jointly influence financial distress. Individually, operational efficiency and operating cash flow exhibit significant effects, whereas the liquidity ratio does not. These results underline the importance of asset utilization efficiency and cash flow performance in explaining financial distress. This study provides empirical evidence that contributes to the financial management literature, particularly in the context of the hotel and restaurant subsector. Keywords: Operating Cash Flow; Operational Efficiency; Financial Distress; Liquidity; Current Ratio; Springate Model